Modification of Power Sprayer as a Pest Spraying Tool for Citrus Plants (Citrus sp.) - Surya, Satria Adi; Mulianda, Pratiwi; Damanik, Annisa Purnamasari; Fitrada, Wathri; Rahmania, Syiffa (Journal of Agriculture, 2025)
This study, titled “Modification of Power Sprayer into a Pest Spraying Tool for Citrus Plants (Citrus Sp),” was conducted in Gunuang Omeh Sub-district, Lima Puluh Kota Regency, from September to October 2024. The objective was to assess the efficiency of a power sprayer and the effectiveness of pest control on citrus plants. The research involved modifying the nozzle of the power sprayer and conducting field tests on a 20 x 20 meter plot. Observations included flow rate, insecticide output capacity, spray distribution, operator walking speed, theoretical field capacity, effective field capacity, spraying efficiency, wind speed, and operator power. In addition, the performance of the power sprayer was compared with that of a knapsack sprayer. Based on the results, the average flow rate was 0.008874 L/s; average droplet size from the power sprayer was 0.3611 mm; average operator walking speed was 0.0413 m/s; average theoretical field capacity was 0.076764 ha/h; average effective field capacity was 0.058789 ha/h; average wind speed was 1.22 km/h; and average operator power was 0.227 kW. The average spraying efficiency of the power sprayer and knapsack sprayer was 76.66% and 60.66%, respectively. These findings indicate that the power sprayer is more efficient than the knapsack sprayer, as it requires less time, less physical effort, and delivers a comparable spray output. Furthermore, the power required by the operator when using the power sprayer is lower than that of the knapsack sprayer.